2015
DOI: 10.1016/j.fcr.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Grouping of early maturing quality protein maize inbreds based on SNP markers and combining ability under multiple environments

Abstract: a b s t r a c tFood insecurity and malnutrition are two major challenges facing rural populations in sub-Saharan Africa (SSA). Hybrids of quality protein maize (QPM) have a crucial role here to play because QPM contains increased lysine and tryptophan concentrations and has a higher biological value than the normal maize. Information on the combining ability and heterotic patterns of QPM inbreds is crucial for the success of hybrid programs in the sub-region. Ninety-one diallel crosses derived from 14 early ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
75
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 52 publications
14
75
1
Order By: Relevance
“…These markers could, therefore, constitute the framework for marker assisted introgression of the op2 trait into maize genotypes [57]. Badu-Apraku et al [20] grouped inbred lines based on GCA of multiple traits and the SNP-based genetic distance methods and they found that the two methods identified two groups each across research environments with close correspondence among the classifications of all the grouping methods in terms of placement of inbreds into the same groups. Moreover, the SNP-based method was found to be most efficient in identifying TZEQI 87 and TZEQI 91 as the best testers for the SNP-based heterotic groups 1 and 2.…”
Section: Molecular Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…These markers could, therefore, constitute the framework for marker assisted introgression of the op2 trait into maize genotypes [57]. Badu-Apraku et al [20] grouped inbred lines based on GCA of multiple traits and the SNP-based genetic distance methods and they found that the two methods identified two groups each across research environments with close correspondence among the classifications of all the grouping methods in terms of placement of inbreds into the same groups. Moreover, the SNP-based method was found to be most efficient in identifying TZEQI 87 and TZEQI 91 as the best testers for the SNP-based heterotic groups 1 and 2.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…[20] QPM hybrids Drought, low soil N, and Striga infested environments in Nigeria SCA effects were higher than GCA indicated the action of nonadditive genes. [21] Inbred lines and single cross hybrids…”
Section: Plant Materials Environment Combinability Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of the new diversity can guide sound strategies for hybrid development and other uses of the germplasm. Molecular markers have been used to investigate genetic diversity and suggest heterotic groupings, hybrid testers, and possible hybrid combinations (Warburton et al 2002;Duarte et al 2004;Lu et al 2009;Wen et al 2011;Semagn et al 2012a;Wegary et al 2013;Akinwale et al 2014;Badu-Apraku et al 2015). Markers could thus be used to ascertain if an increase in diversity levels in mid-altitude maize germplasm can be measured following introduction of QPM germplasm from tropical breeding programs.…”
Section: Introductionmentioning
confidence: 99%